The Role of the School Committee in the Implementation of School-Based Management in the Sidoarjo District - Nuning Nurna Dewi; Achmad Fathoni Rodli; Niswatin Niswatin; Insan Suwanto (STKIP Singkawang, 2022)
The role of school committees in improving the quality of education through the concept of School-Based Management (SBM) is motivated by changes in education policy from centralization to decentralization as a consequence of regional autonomy policies. This change has a positive impact, namely encouraging community participation to participate in improving the quality of education. The purpose of this study was to analyze the role of school committees in the implementation of School-Based Management (SBM) policies. Data were collected through document studies and interviews of public and private SMP/MTs in Sidoarjo Regency with a sample of 24 schools, while data analysis was carried out descriptively. The results showed that the role of the school committee was quite high. The advisory role averaged 86%, the supporting role reached an average of 90%, the controlling role averaged 53%, and the mediating role reached an average of 83%. From this percentage, it is hoped that the role of the school committee will have an impact on improving the quality of education continuously.